Translation and validation of MHAQ score in local language Urdu in Patients with rheumatoid arthritis presenting in a tertiary care center of Pakistan - Ehsan, Amna; Mushtaq, Samina; Salim, Babur; Samreen, Saba; Gul, Haris; Nasim, Amjad (Journal of the Pakistan Medical Association, 2022)
Objective: To translate and validate the Modified Health Assessment Questionnaire from English to Urdu. Method: The validation study was conducted at the Rheumatology outpatient department of Fauji Foundation Hospital, Rawalpindi, Pakistan, from July 1 to September 30, 2019. Two translators were given the modified health assessment questionnaire for translation from English to Urdu. It was then back-translated by two independent translators. The translated version of the tool was applied to rheumatoid arthritis patients to check for reliability, test-retest and internal consistency. It was applied to another group of patients to check for criterion validity. Reliability analysis was checked by applying Cronbach alpha. Criterion validity was checked by assessing disease activity score-28 and its correlation with Modified Health Assessment Questionnaire. Data was analysed using SPSS 23. Results: Of the 30 patients in the initial testing, 28(93%) were females and 2(6.6%) were males, with an overall mean age of 38±13.2 years. Of the 100 patients in the second group, 97(97%) were women and 3(3%) were men, with an overall mean age of 42±12.37 years. The mean disease duration of the cohort was 8.4±4.8 years. The Cronbach alpha value was 0.797 and interclass coefficient was 0.7, reflecting good reliability. A significantly high correlation between Modified Health Assessment Questionnaire and disease activity score-28 was noted along with pain, tenderness, swollen joints, patient global assessment, age and erythrocyte sedimentation rate (p<0.05), while poor correlation was found with gender, disease duration, rheumatoid arthritis factor and anti-cyclic citrullinated peptide antibody (p>0.05). —Continue